2013
DOI: 10.4265/bio.18.163
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Activity of Isothiocyanates (ITCs) Extracted from Horseradish (Armoracia rusticana) Root against Oral Microorganisms

Abstract: The antimicrobial activity of isothiocyanates (ITCs) extracted from horseradish root was investigated against oral microorganisms: 6 strains of facultative anaerobic bacteria, Streptococcus mutans, Streptococcus sobrinus, Lactobacillus casei, Staphylococcus aureus, Enterococcus faecalis and Aggregatibacter actinomycetemcomitans; one strain of yeast, Candida albicans, and 3 strains of anaerobic bacteria, Fusobacterium nucleatum, Prevotella nigrescens, and Clostridium perfringens. The ITCs extracted from horsera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(26 citation statements)
references
References 19 publications
3
22
1
Order By: Relevance
“…Park et al . () also reported that antimicrobial activity of AITC against Gram‐positive bacteria was greater than that of Gram‐negative bacteria, mainly due to the structural differences in the bacterial cell wall.…”
Section: Resultsmentioning
confidence: 85%
See 3 more Smart Citations
“…Park et al . () also reported that antimicrobial activity of AITC against Gram‐positive bacteria was greater than that of Gram‐negative bacteria, mainly due to the structural differences in the bacterial cell wall.…”
Section: Resultsmentioning
confidence: 85%
“…In addition, the inhibition zone against Gram-positive bacteria (L. monocytogenes) was larger than that of Gramnegative bacteria (E. coli O157:H7). Park et al (2013) also reported that antimicrobial activity of AITC against Gram-positive bacteria was greater than that of Gram-negative bacteria, mainly due to the structural differences in the bacterial cell wall.…”
Section: Thermal Properties Of the Jfp Films Containing Wementioning
confidence: 99%
See 2 more Smart Citations
“…Especially the isothiocyanates, which also give cabbages and mustards their pungent flavour, are toxic or deterrent to a wide range of herbivores and pathogens (Brown and Morra, 1997;Hopkins et al, 2009;Park et al, 2013). Another property of isothiocyanates is that they contribute to human health.…”
Section: Introductionmentioning
confidence: 99%